2007
DOI: 10.1021/la0628571
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Templated Magnetic Nanowires with Different Compositions:  Fabrication and Analysis

Abstract: The structure and magnetic properties of different types of templated wires are compared in this study. A long DNA molecule was used to guide the assembly of pyrrolidinone-capped Fe2O3 and CoFe2O3 particles as well as polylysine-coated gold nanoparticles. The resulting DNA-templated wires were stretched onto silicon oxide surfaces using a receding meniscus procedure. The coated, stretched, and surface-bound wires were characterized using atomic force microscopy (AFM), magnetic force microscopy (MFM), and spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 51 publications
1
51
0
Order By: Relevance
“…Earlier, Braun et al demonstrated that DNA has desired properties for templating metal structures [5]. Our group has shown that DNA can be used for the assembly of magnetic and metallic nanoparticles, creating DNA template nanowires [6]. Also, with the use of restriction endonucleases and DNA ligase, it was demonstrated through gel experiments that DNA template nanowires can be clipped at specific sequences and ligased back together [7].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Earlier, Braun et al demonstrated that DNA has desired properties for templating metal structures [5]. Our group has shown that DNA can be used for the assembly of magnetic and metallic nanoparticles, creating DNA template nanowires [6]. Also, with the use of restriction endonucleases and DNA ligase, it was demonstrated through gel experiments that DNA template nanowires can be clipped at specific sequences and ligased back together [7].…”
Section: Introductionmentioning
confidence: 94%
“…The fabrication of DNA template nanowires is described in detail in Kinsella and Ivanisevic [6]. For a 1:1 DNA:NP (mass ratio) nanowire, 25 L of 536 g/mL unmethylated lambda phage DNA (Promega) in 1× MULTI-CORE TM Buffer (Promega) was added to 25 L of 1 mg/mL nanoparticle solution.…”
Section: Synthesis Of Dna Template Nanowiresmentioning
confidence: 99%
“…The ligands used in the study were (2-mercaptoethyl)trimethylammonium iodide, [2-(2- obtained by assembling positively charged, 2-pyrrolidonestabilized, 4.1-nm-sized iron oxide or 3.4-nm-sized cobalt iron oxide nanoparticles on the negatively charged DNA backbone. 81 Extended DNA -FePt nanoparticle aggregates were assembled by Rotello et al through electrostatic interaction by using 37-mer duplex DNA. 82 The positively charged, 7-nm-sized FePt nanoparticles in this study were stabilized with 10-carboxydecyltrimethylammonium bromide and 11-mercaptoundecyltrimethylammonium chloride.…”
Section: Dna-based Systemsmentioning
confidence: 99%
“…41,42 We finally propose that the occurrence of areas of short-range order in twodimensional assemblies of nanoparticles may be of use for magnetic data storage purposes. It has been discussed elsewhere 1 that for the use of two-dimensional assemblies of magnetic nanoparticles, it would be "highly desirable that the ordered particles have a common magnetic easy axis."…”
Section: Initial Momentmentioning
confidence: 99%